A highly efficient auxin-producing bacterial strain and its effect on plant growth - Seunghye Park (SpringerOpen, 2021)
Abstract Background Various bacteria promote plant root growth in the rhizosphere, as a measure of securing and enlarging their ecological niche. These interactions are mediated by plant growth regulators (PGRs) such as auxin, and indole-3-acetic acid (IAA) is one of the physiologically active auxin. In this study, we isolated an unusual bacterial strain from food process waste with high efficiency and demonstrated its effects on plant rooting and early-stage growth. Results The efficiency of this bacterial strain in producing IAA was 16.6 mg/L/h in Luria-Bertani broth containing 0.05% l-tryptophan (Trp) at room temperature (24 ± 2 °C). Its IAA production was highly dependent on the presence of precursor, Trp. This bacterium was identified as Ignatzschineria sp. by 16S rDNA sequencing. Its bacterial culture supernatant (BCS) enhanced plant root initiation, root growth, and plant growth in the early stages. The root mass formed BCS-treated in apple mint cuttings was twofold of that formed in the control. The root number and length were 46% and 18% higher, respectively, in BCS-treated chrysanthemum cuttings than in the control. Conclusions These results show that the BCS of Ignatzschineria sp. CG20001 isolate obtained in this study can be used for agricultural applications. In addition, the novelty of this strain makes it a valuable genetic resource for biotechnological applications.